2002
DOI: 10.1152/japplphysiol.00739.2001
|View full text |Cite
|
Sign up to set email alerts
|

Muscle type-specific response of HSP60, HSP72, and HSC73 during recovery after elevation of muscle temperature

Abstract: An original method to induce heat stress was used to clarify the time course of changes in heat shock proteins (HSPs) in rat skeletal muscles during recovery after a single bout of heat stress. One hindlimb was inserted into a stainless steel can and directly heated by raising the air temperature inside the can via a flexible heater twisted around the steel can. Muscle temperature was increased gradually and maintained at 42 degrees C for 60 min. Core rectal and contralateral muscle temperatures were increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
80
2
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 37 publications
(58 reference statements)
11
80
2
1
Order By: Relevance
“…The PEST find tool from the European Molecular Biology Network (EMBnet) was used to examine Hsp70B 0 for a potential PEST site, a putative degradation signal, which was found to be absent from the protein sequence. Hsp72 levels are also rapidly induced, but typically remain stable following heat shock, and elevated protein levels can be detected for a number of days (Joyeux et al, 2000;Oishi et al, 2002). We showed here that Hsp70B 0 reaches its highest level at 12 h and is undetectable at 24 h. This suggests that Hsp70B 0 is used transiently in response to stress and it is Fig.…”
Section: Discussionsupporting
confidence: 52%
“…The PEST find tool from the European Molecular Biology Network (EMBnet) was used to examine Hsp70B 0 for a potential PEST site, a putative degradation signal, which was found to be absent from the protein sequence. Hsp72 levels are also rapidly induced, but typically remain stable following heat shock, and elevated protein levels can be detected for a number of days (Joyeux et al, 2000;Oishi et al, 2002). We showed here that Hsp70B 0 reaches its highest level at 12 h and is undetectable at 24 h. This suggests that Hsp70B 0 is used transiently in response to stress and it is Fig.…”
Section: Discussionsupporting
confidence: 52%
“…It has been clarified that newly synthesized mitochondrial precursor proteins are transported into the mitochondria and refolded by mtHSP and HSP72 39) . Heat stress dramatically increases mtHSP and HSP72 protein contents in skeletal muscle 20,40) . One could speculate that an increase in mtHSP and HSP72 may promote transportation efficiency into the mitochondria and the folding process and then enhance mitochondrial adaptations.…”
Section: Heat Stress Activates Regulatory Factors Of Mitochondrial Bimentioning
confidence: 99%
“…Exercise in hot and humid environments increases physiological strain on the body in comparison with temperate conditions (Galloway and Maughan 1997). Combined with exercise (exercise-heat stress), environmental manipulation to induce hyperthermia (Fehrenbach et al 2001;Oishi et al 2002;Moran et al 2006;Whitham et al 2007;Sandström et al 2008;Iguchi et al 2012) have been reported as stimuli for further increasing eHsp72 compared to exercise alone. Indeed a strong relationship exists between plasma eHsp72 and core temperature (Ruell et al 2006;Sandström et al 2009).…”
Section: Introductionmentioning
confidence: 99%